Adipose-Derived Stem Cells Protect Ischemia-Reperfusion and Partial Hepatectomy by Attenuating Endoplasmic Reticulum Stress - Jiao, Zhihui; Liu, Xiaoning; Ma, Yajun; Ge, Yansong; Zhang, Qianzhen; Liu, Boyang; Wang, Hongbin (Frontiers in Cell and Developmental Biology, 2020)
Ischemia-reperfusion (IR) is an inevitable complication of liver surgery. Recent studies indicate a critical role of endoplasmic reticulum stress (ERS) in hepatic IR. Mesenchymal stem cells (MSCs) have proven to be an effective tool for tissue regeneration and treatment of various diseases, including that of the liver. However, the mechanisms underlying the therapeutic effects of stem cells on hepatic IR injury (IRI) are still poorly understood, especially in the context of ERS. In this study, we established a porcine model of hepatic IRI and partial hepatectomy, and transplanted the animals with adipose-derived mesenchymal stem cells (ADSCs) isolated from miniature pigs. ADSCs not only alleviated the pathological changes in the liver parenchyma following IRI, but also protected the resident hepatocytes from damage. Mechanistically, the ADSCs significantly downregulated ERS-related proteins, including GRP78, p-eIF2α, ATF6 and XBP1s, as well as the proteins involved in ERSinduced apoptosis like p-JNK, ATF4 and CHOP. Taken together, ADSCs can alleviate hepatic IRI by inhibiting ERS and its downstream apoptotic pathways in the hepatocytes, indicating its therapeutic potential in liver diseases.